WNT signaling pathway gene polymorphisms and risk of hepatic fibrosis and inflammation in HCV-infected patients. - Yanhong Liu; Hashem B El-Serag; Li Jiao; Juseog Lee; David Moore; Luis M Franco; Shahriar Tavakoli-Tabasi; Spiridon Tsavachidis; Jill Kuzniarek; David J Ramsey; Donna L White (PLoS ONE, 2013)
Chronic hepatitis C infection is the leading cause of hepatocellular carcinoma (HCC), a highly lethal malignancy with rapidly increasing prevalence in the United States. Little is known about genetic variations and HCC risk. This study aimed to determine if genetic variation in Wnt signaling pathway genes are associated with advanced hepatic fibrosis and inflammation risk in a hepatitis C virus (HCV) infected population.We performed a genetic association cross-sectional study evaluating single nucleotide polymorphisms (SNPs) in 58 candidate genes and risk of FibroSURE-Acti Test determined advanced fibrosis (F3/F4-F4 advanced cases vs. F0-F3 mild controls) and inflammation (A2/A3-A3 advanced cases vs. A0-A2 mild controls). We calculated odds ratios (ORs) and 95% confidence intervals (CIs) employing multivariate logistic regression. Haplotypes were inferred by the HAPLO.STAT program, interactions were evaluated using multifactor dimensionality reduction (MDR) analysis.Among 425 chronically HCV-infected male veterans, 155 (37%) had advanced fibrosis and 180 (42%) had advanced inflammation. Of 3016 SNPs evaluated, eight were significantly associated with fibrosis risk (e.g., SFRP2 rs11937424: OR = 2.19, 95% CI 1.48-3.23, P = 0.00004), and seven were significantly associated with inflammation risk (e.g., SFRP1 rs16890282: OR = 2.15, 95% CI 1.39-3.16, P = 0.0004). MDR analysis identified overweight/obese, SOST rs1405952, SFRP2 rs11937424, and FZD4 rs11234870 as the best interaction model for predicting risk of fibrosis; whereas race/ethnicity, FZD1 rs1346665, and TBX3 rs1520177 as the best interaction model for predicting risk of inflammation.Polymorphisms in several genes involved in the Wnt signaling pathway were associated with hepatic fibrosis or inflammation risk in HCV-infected males. Additional studies in other multi-ethnic HCV cohorts are needed to validate our findings in males and to assess if similar associations exist in chronically HCV-infected females.